A case of extraskeletal chondroma in the left inguinal region - Alexey Shabunin; Ivan Lebedinsky; David Dolidze; Zurab Bagatelia; Ekaterina Solomonova; Anna Bumbu; Serghei Covantsev (Folia Medica)
Extraskeletal chondromas are rare benign neoplasms comprising mature hyaline cartilage. A distinctive feature of these tumors is that they develop in soft tissues away from bone and cartilage. Extraskeletal chondromas account for 1.5% of benign soft tissue tumors. They occur predominantly at 30-60, in males, and in the hand or foot. In only 4% of cases, the tumor is located not on the extremities. Patients predominantly complain of increased mass, rarely on pain or a pulling sensation. The literature on the chondromas of the anterior abdominal wall is scarce. We present a rare case of a large extraskeletal left inguinal chondroma in a 71-year-old patient. The mass was over 6 cm large, and this is the only case of inguinal chondroma described in the literature. The mass was resected with surrounding tissues (a surgical margin of 1 cm) under combined endotracheal anesthesia and the histology confirmed the tumor to be a chondroma.